IMPROVEMENT OF CONTROL IN THE SYSTEM OF MANAGEMENT OF ECONOMIC SECURITY OF THE ENTERPRISE (Development Service Industry Management, 2025)
The article analyzes the importance of control in the system of economic security of the enterprise. Since production and business under modern conditions require effective control in the economic security management system of the enterprise. To achieve this goal, it is important to implement a system of risk monitoring and analysis, monitor financial indicators and optimize production processes. It is also important to have clearly defined crisis management procedures and action plans in case of problems. In order to successfully improve control in the economic security management system of the enterprise, it is recommended to involve qualified specialists with relevant experience and use modern technologies in this field. It is also necessary to create mechanisms for constant monitoring and updating of the control system in order to ensure constant development and improvement of the efficiency of management of economic security of the enterprise. It has been proven that risk control and assessment are important elements of any system management. It is substantiated that in order to increase the economic security of the enterprise, it is important to develop risk management strategies. This will allow identification of potential threats and ways to avoid them or reduce the impact on the company's activities. It is also important to take into account internal and external factors that can affect the success of the business. It is noted that the application of effective methods in practical activities is key to successful enterprise management. Effective methods help to optimize processes, reduce costs, improve productivity and ensure business stability. It is important to constantly improve and implement new management methods to achieve success in the market.
Keywords: economic security; system approach; complex approach; control elements; risk monitoring